Analisis Efektivitas dan Kontribusi Pajak Daerah, Retribusi Daerah, Pengelolaan Kekayaan Daerah yang Dipisahkan dan Lain-lain PAD yang Sah Pada Kabupaten Gunungkidul Tahun 2012-2016 - Edwin Alrin Balubun (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research is measuring how much the contribution of local taxes, local retribution, the result of the management of local wealth separately, efficiency of legitimate local revenues hane large contribution to regional income. Study case in Gunungkidul regency years of 2012 – 2016. In this research we use descriptive statistic as method analysis to know how much each component of regional income (local taxes, local retribution, the result of the management of local wealth separately, efficiency of legitimate of local revenues have large contribution to regional income) in Gunungkidul regency. This research data is obtained from the financial management and asset of Gunungkidul regency. Population and the sample of the research is the report on realization of local revenue years of 2012 – 2016 componen Gunungkidul regency. The result show that local taxex, local retribution, the result of the management of local wealth separately, efficiency of legitimate local revenues have large contribution to region income are fluctuated every year. The highest regional income is on 2015 123 percent the lowest is on 2012 99 percent then local taxes, local retribution, the result of the management of local wealth separately, efficiency of legitimate local revenues have large contribution to regional income are decreasing and increasing fluctuated. The avarege of contribution percentage of 2015 is the highest on other component of legitimate local revenues and the lowest contribution is on 2014 and 2015 on component the of the managemen of local, wealth separatel is 5 percent but is if welook from all over component in evert years the conclusion is for sector of the management of local wealth separately 7 percent has lowest contributon to regional income 2016 in Gunungkidul regency. Key words : effectvenes local taxes, local retribution, the result of the management of local wealth separately.